BETULIN 3, 28-DIPHOSPHATE AS AN ACTIVATOR OF ANTIOXIDANT ENZYMES IN COMBINATION WITH AMINES AND AN ENHANCER OF BACTERICIDAL AND FUNGICIDAL ACTIVITY OF BENZALKONIUM CHLORIDE - MELNIKOVA, NINA; MALYGINA, DARINA; KLABUKOVA, IRINA; SOLOVEVA, ANNA; AULOVA, ELENA (International Journal of Applied Pharmaceutics, 2026)
Objective: The work was aimed to study properties of nanosuspensions of betulin diphosphate and its sodium salt in compositions with amines – trisamine, meglumine and benzalkonium chloride, for design of antioxidant medicines and enhance bactericidal and fungicidal activity of benzalkonium chloride. Methods: This research work included the preparation and study of nanosuspensions. Nanoparticles formation was controlled using FTIR, UV and NMR spectrometry, PXRD, zeta-potential measurement and SEM visualization. Oxidoreductase activity was studied by specific activity of superoxide dismutase, catalase, glutathione reductase, glucose-6-phosphate dehydrogenase and aldehyde dehydrogenase. Paecilomyces variotii, Aspergillus terreus, Penicillium chrysogenum, Staphylococcus aureus and Staphylococcus epidermidis were used in study. Results: Betulin diphosphate or its sodium salt in the presence of amines are capable of self-organization and formation of high positive charged nanoparticles (zeta potential from+37 to+51 mV) with various morphologic structures that allow to obtain transparent nanosuspensions. Concentration of aged sodium salt of betulin diphosphate with amines was at least 0.644% that was higher than one of aqueous dispersions without amines. In vitro experiments on rat blood showed an increase in the specific activity of antioxidant enzymes under the action of all studied compositions. Sodium salt of betulin diphosphate showed synergetic effect of fungicidal and bactericidal properties of a known antimicrobial agent benzalkonium chloride in composition. Conclusion: The revealed biological activity of new compositions of betulin diphosphate with amines can be useful in the treatment of various skin diseases.